165k views
3 votes
How do you do the equation -3(n-5) = 7-4ne

User Daouda
by
4.7k points

1 Answer

6 votes

Answer:

n = -8

Explanation:

We assume you want to solve the equation

-3(n -5) = 7 -4n

Use the distributive property to eliminate parentheses. Then you have a 3-step linear equation that can be solved in the usual way.

-3n +15 = 7 -4n . . . . . eliminate parentheses

n +15 = 7 . . . . . . . . . . . add 4n to both sides

n = -8 . . . . . . . . . . . . . . subtract 15 from both sides

If the coefficient of n were not 1, then you would divide by that. Here, the "3-step" equation took only 2 steps to solve.

The solution is n = -8.

User Bogdan Popa
by
5.8k points